PELATIHAN PEMBUATAN VIDEO PEMBELAJARAN DI TK. AL-JABBAR BLIMBING KOTA MALANG - Ahmad Fauzi; Eko Boedi Santoso; Ayu Sulasari; Kartika Indah; Fahmi Muhammad (Jurnal Pengabdian Polinema Kepada Masyarakat, 2020)
The targets of community service activities are the teachers or educators of Malang City's AlJabbar Kindergarten (TK), and other private kindergartens around them. The selection of private Al-Jabbar Kindergarten teachers is because the existing facilities of the school are inadequate, so there is a need for learning media assistance and enhancement of the quality of creative teachers in the learning process. This activity aims to help improve the quality of the learning process by increasing the ability of teachers in this school, so that learning is better and more enjoyable. PKM activities include: Introductory material, Learning media demo, Provision of Materials, practical training in making instructional media, Planning learning media according to topic, making instructional media according to plan, discussion and evaluation of learning media and finally improvement in making instructional media..